Evolution of Adoption from Roman Law to Modern Law - Ignjatović, Marija V; Kitanović, Tanja B (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The work is dedicated to the evolution of adoption practice from ancient Roman law to modern law. Adoption represents ancient social and legal practice which has during time changed manifestations and the causes it served. Adoption in ancient Rome served the interests of pater familias without biological posterity. Adoption practice benefited the continuance of families and the family cult of adopters, whose family lines, with no natural posterity, were threatened to become extinct. After the stagnation in the feudal epoch, adoption was reaffirmed in the bourgeois law. Civil codes in European countries, whose legal systems were built on the foundations of the ancient Roman legal tradition, originally favoured the interests of individuals with no biological children, who were granted to extend their families by adopting, and hence transfer their assets on the obtained heirs. After the wars in the 20th century, which led to a rapid increase in the number of parentless children, the concept of adoption was radically changed, so that since that time the adoption has primarily served the interests of the adopted children and the care for them in the adoptive families. Adoption becomes a form of a social, legal family protection of children without adequate parental care, and that is the most desirable form to provide for children, for the adoptee completely integrates with the adoptive family and takes the right of the born child, where the family environment provides and encourages the optimal mental and physical development of the child.
Keywords: modern law; bourgeois law; feudal law; ancient Roman law; adoptee; adoptive parents; adoption